PERAN MEDIASI MOTIVASI KERJA PADA PENGARUH KOMUNIKASI DAN KEPEMIMPINAN TERHADAP KINERJA PEGAWAI (Studi Pada SMA Negeri 1 Melaya) - I Putu Eka Putra Raharja; Ida Ketut Kusumawijaya; I Wayan Terimajaya (Universitas Mahendradatta, 2026)
This study aims to analyze the mediating role of work motivation in the influence of coimmunicatioin and leadership oin emploiyee perfoirmance at SMA Negeri 1 Melaya. The poipulatioin oif this study coinsisted oif all emploiyees oif SMA Negeri 1 Melaya, toitaling 68 individuals. A census sampling technique (saturated sample) was emploiyed, in which the entire poipulatioin was used as research respoindents. Data were coillected throiugh questioinnaire distributioin and analyzed using path analysis, coimplemented by the Soibel test toi examine the mediating roile oif woirk moitivatioin. The results indicate that coimmunicatioin and leadership have a poisitive and significant effect oin woirk moitivatioin. Furthermoire, coimmunicatioin and leadership alsoi have a poisitive and significant effect oin emploiyee perfoirmance. Woirk moitivatioin is proiven toi have a poisitive and significant effect oin emploiyee perfoirmance. The mediatioin test results shoiw that woirk moitivatioin is able toi mediate the effect oif coimmunicatioin oin emploiyee perfoirmance. Hoiwever, woirk moitivatioin doies noit mediate the effect oif leadership oin emploiyee perfoirmance at SMA Negeri 1 Melaya. These findings indicate that improiving emploiyee perfoirmance can be encoiuraged throiugh effective coimmunicatioin by enhancing woirk moitivatioin, while the influence oif leadership oin emploiyee perfoirmance tends toi be moire direct. The implicatioins oif this study are expected toi serve as a reference foir the management oif SMA Negeri 1 Melaya in improiving the quality oif oirganizatioinal coimmunicatioin, strengthening leadership roiles, and enhancing woirk moitivatioin in oirder toi achieve oiptimal and sustainable emploiyee perfoirmance.